Seasonal scenario planning for matching seed supply and demand: Workshop slides - Steinke, Jonathan; Ortíz Crespo, Berta (2022)
These slides are meant to be used jointly with the "seasonal scenario planning: workshop format" and the MS Excel tool. The presentation describes the different concepts involved in scenario planning, including examples.